Pharmacokinetics, Bioavailability, and Swallowing Safety With Riluzole Oral Film. Issue 1 (27th September 2022) - Wymer, James; Apple, Stephen; Harrison, Antoinette; Hill, Bryan Alan
Abstract: Dysphagia is highly prevalent in patients with amyotrophic lateral sclerosis (ALS). Riluzole is a US Food and Drug Administration‐approved treatment for ALS. Riluzole oral film (ROF; Exservan™) contains riluzole in a polymer‐based film matrix. The ROF is administered by placing on the tongue, where it dissolves and the drug is ingested with the saliva. Two clinical trials assessed the safety and tolerability of the ROF. Bioavailability and pharmacokinetics (PK) were evaluated in an open‐label, randomized, single‐dose, replicate crossover study of 50 mg of ROF and riluzole 50‐mg tablets in 32 healthy volunteers. The second study was a videofluoroscopic swallowing examination conducted with nine patients with ALS before and after receiving a single dose of 50 mg of ROF. The primary outcome was change on penetration‐aspiration scale (PAS) scores from pre‐ to post‐dose. Overall, the PK parameters for ROF and riluzole tablets were comparable between treatments and administrations when administered under fasting conditions. Administration of ROF with food resulted in a 15% reduction in area under the curve and a 45% reduction in maximum serum concentration. A total of 44 treatment‐emergent adverse events (AEs) were reported in the study; all were mild in severity. No serious AEs were observed and no subjects discontinued due to AEs. In the swallowing study, very little numerical or categorical change was observed following the dose of ROF. No evidence of deterioration of swallowing function was observed post‐dose. The ROF was bioequivalent to riluzole tablets, was well tolerated, and had no detrimental effect on swallowing.